The Effect of Financial Literacy, Financial Knowledge, Financial Attitudes and Personality on Financial Management Behavior in MSME - Rizka Septiana Putri; Naelati Tubastuvi; Ika Yustina Rahmawati; Hermin Endratno (Universitas Muhammadiyah Jakarta, 2023)
The research was conducted with the aim of examining the influence of financial literacy, financial knowledge, financial attitudes and personality on financial management behavior. The subjects in this examine were Micro, Small and Medium Enterprises (MSMEs) in Banyumas Regency with a population of 8,542 MSMEs and the sample in this observe was 159 MSMEs. Information were dissected the utilizing validity test, reliability test, descriptive analysis, classical assumption test, and multiple regression test. The study demonstrates that financial literacy, financial knowledge, financial attitudes, and personality traits have a significant and positive impact on financial management behavior. Based on this research, financial management behavior for MSME is very important, MSME must understand how important it is to understand financial literacy, financial knowledge, financial attitudes and personality. Thus, some Banyumas MSMEs have implemented good financial management behaviors and can be an example for other MSMEs.